PROFESSIONAL AND PEDAGOGICAL COMPETENCE OF EDUCATIONAL AND METHODOLOGICAL CENTERS TEACHERS IN THE SPHERE OF CIVIL DEFENSE: STRUCTURE AND CONTENT - Demkiv Anna (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
The aim of the article is to identify the structure and the content of professional and pedagogical competence of educational and methodological centers teachers in the sphere of civil defense based on the analysis of the higher educational standards in the specialty 011 «Education, pedagogical science» for the second (master’s) level of higher education and in the specialty 263 «Civil Security» for the second (master’s) level of higher education and expert survey. In order to realize the purpose of the research the author used the following methods of investigation: structural analysis – to identify the structure of professional and pedagogical competence of educational and methodological centers teachers in the sphere of Civil defense; statistical analysis of databases: National repository of academic texts (NRАТ), searching systems and databases of scientific citations which come from all publications using such services as Cited-by by Crossref and support Initiative for Open Citations (Open Ukrainian Citation Index – OUCI), repository of scientific periodicals of National Library named after V.I. Vernadskyi; expert assessment of the content of professional and pedagogical competence components; critical analysis of source base on the research problem; and infographics for visualization of the obtained results. Based on the results of studying scientific sources and expert assessment of the content of professional and pedagogical competence components of the educational and methodological centers teachers in the sphere of Civil defense it is identified that some of them are close in their meaning but some structural components differ only in their name. Besides, it was found out that the most widespread professional and pedagogical competence components of the teachers are as follows: social, cognitive and technological (cognitive) and motivational. The structure of professional and pedagogical competence of the educational and methodological centers teachers in the sphere of Civil defense being a complex of interconnected components such as motivational and valuable, cognitive, active and personal and professional ones was designed based on the expert survey results. Moreover, content of professional and pedagogical competence of the educational and methodological centers teachers in the sphere of Civil defense was justified. It reflects binary character of their activity – both civil defense professionals and teaching professionals, which prompts them to continuous professional development. It should be mentioned that the orientation of the individual in their activities on values which ensures their activity, initiative, deep faith in their own strength and concern for others was defined as the main content of the motivational and valuable component. The content of the cognitive component is a multilevel system of providing the opportunity to carry out a wide range of cognitive processes such as thinking, understanding, remembering, attention and perception. The development of the activity component provides the ability of practical use of practical and theoretical knowledge and technologies for improving trainees’ qualifications in different categories in the sphere of civil defense. The content of the personal and professional component is defined as a complex of personal qualities which ensures their self-organization at a high level of professional development based on reflection, and it is the basis for improving pedagogical skills. The structure and the content of professional and pedagogical competence of the educational and methodological centers teachers in the sphere of Civil defense are advisable to use to design the professional development program in the postgraduate system as well as in the process of methodical work.